2018
DOI: 10.1123/rsj.2016-0030
|View full text |Cite
|
Sign up to set email alerts
|

Sport Club Participation and Health-Related Outcomes in College Students: Comparisons by Sex and Academic Classification

Abstract: Using the theory of student involvement, the purpose of this study was to compare sport club participation and health-related outcomes, as well as the association between these two variables by sex and academic classification among college students. Participants were 127 sport club members recruited from a university in the southwestern United States. MANOVA analyses indicated that males reported more recreation center visits, greater sport club satisfaction, and lower subjective vitality than females; freshme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…e body composition indicators of the study subjects changed greatly, among which lean body mass and muscle mass increased significantly. ere was no significant change in fat mass in boys before and after exercise, but there was a significant change in girls [23]. In addition, there was no significant change in the weight data of the researchers themselves (P > 0.05).…”
Section: Discussionmentioning
confidence: 78%
“…e body composition indicators of the study subjects changed greatly, among which lean body mass and muscle mass increased significantly. ere was no significant change in fat mass in boys before and after exercise, but there was a significant change in girls [23]. In addition, there was no significant change in the weight data of the researchers themselves (P > 0.05).…”
Section: Discussionmentioning
confidence: 78%
“…Studies also investigated the experiences of students with physical disabilities (e.g., Devine, 2016; Dysterheft et al, 2018; McKay et al, 2019), the design of adaptive programing (e.g., Fines & Block, 2021; Gillies & Dupuis, 2013; Shapiro et al, 2020) and the prevalence of programing for vulnerable populations (e.g., Horacek et al, 2014; Zuest et al, 2021). Some scholars also examined participation trends among students registered in specific educational programs (e.g., Gathman et al, 2017; Slade & Kies, 2015), differences between undergraduate and graduate students (e.g., Henchy, 2013) and participation among first year students (e.g., Chu & Zhang, 2018; Deng et al, 2021; Helms & Moiseichik, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, mental health promotion and helping students become physically active on a regular basis are recommendations for improvement in mental wellbeing among students [ 40 – 42 ]. A US-based study showed that sports club participation in college students is associated with positive health-related outcomes [ 41 ]. Also aligned, Australian students with higher sports club involvement have a positive and significant association with social-emotional wellbeing indicators, such as happiness, resilience, and body image, whereas low involvement in sports club is associated with a greater incidence of mental health diagnosis [ 43 ].…”
Section: Discussionmentioning
confidence: 99%